2016
DOI: 10.2147/ijn.s98080
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of finasteride capsules-loaded drug nanoparticles: formulation, optimization, in vitro, and pharmacokinetic evaluation

Abstract: In this study, optimized freeze-dried finasteride nanoparticles (NPs) were prepared from drug nanosuspension formulation that was developed using the bottom–up technique. The effects of four formulation and processing variables that affect the particle size and solubility enhancement of the NPs were explored using the response surface optimization design. The optimized formulation was morphologically characterized using transmission electron microscopy (TEM). Physicochemical interaction among the studied compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…[23][24][25] PVA was added to the aqueous phase as a stabilizer to produce small size and stable NPs. 26,27 The possible formulation parameters affecting the preparation of the NPs were optimized to achieve the optimum concentration of PLGA in the organic solvent, organic to aqueous phase ratio and PVA concentration in the aqueous phase. Central composite experimental design was used as a tool used to investigate the effects of the independent variables (X1-X3) on the dependent variables (Y1-Y2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] PVA was added to the aqueous phase as a stabilizer to produce small size and stable NPs. 26,27 The possible formulation parameters affecting the preparation of the NPs were optimized to achieve the optimum concentration of PLGA in the organic solvent, organic to aqueous phase ratio and PVA concentration in the aqueous phase. Central composite experimental design was used as a tool used to investigate the effects of the independent variables (X1-X3) on the dependent variables (Y1-Y2).…”
Section: Resultsmentioning
confidence: 99%
“…Above this critical micelle concentration, there is a less surfactant surface adsorption since the micelle molecules begin to compete for the adsorption at the solid particles; this effect results in destabilization of the prepared NPs and therefore contributed to increase in the particle size. [26][27][28][29] Second, increase in the concentration of PVA leads to increase in the viscosity of the aqueous phase, which in turn decreases the rate of PLGA solidification and so formation of large size particles. Results also revealed that, as the concentration of PLGA was increased, the particle size of the prepared NPs was increased.…”
Section: Effect On Particle Sizementioning
confidence: 99%
“…The later sustained release indicated that drugs might be stably retained in the lipid matrix before slow release by drug diffusion. 49 Retardation of drug release in NLCs may be ascribed to the distribution of drugs in the lipid matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro dissolution analyses were carried out for Nanoparticles filled capsules 26 in dissolution test apparatus (Labinda, Disso) using 900mL of dissolution media, 0.1N HCl of pH value 1.2 for 2h and phosphate buffer of pH value 6.8 for 24 h at 37±0.5°C. Samples were introverted in pre-determined intervals up to 24h.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%